A 23Na NMR study on the environment and mobility of sodium ions in complex food matrices and model systems - Shao, Jiaqian (2019)
A high sodium diet increases the risk of mortality and high blood pressure morbidity. With the aim of reducing the sodium content, different food systems (liquid, semi-solid and solid) have been studied. Low-field NMR spectrometry (23 MHz) was only used for liquid systems (reported in a previous dissertation) due to the limitations of the low field and long deadtime. A Bruker 600 MHz NMR spectrometer with solution and solid probes has been used to determine the mobility and form of sodium in the other systems.